United States and Japan - Reischauer, Edwin O. (Cambridge, 1957)
The admission of Japan to the United Nations in December last can be taken as marking the end of a cycle in that country's i postwar history. When General MacArthur arrived on the Battleship Missouri eleven years before, Japan lay utterly defeated and impotent in the face of her conquerors. In the en suing years she underwent a wide-reaching economic recovery. and, far more important, achieved a program of reform whose extent and breath-taking acceleration were perhaps without parallel in history. As a result of these developments, and even more, of her prewar experience, Japan has become the front runner of democracy in Asia, and American policy in that vast area hinges in very substantial measure on the success with which the Japanese maintain and extend free institutions in the coming years. At a time when the competition of the free and communist worlds is joined to win the allegiance of the teeming populations still uncommitted, the future of Japanese democ racy poses a problem of capital significance for American policy. It is a tragic fact that, despite the central role which the United States has played in Japan's recovery and reform, the American people are still remote from that country in both interest and knowledge. It is precisely this situation which gives the present book its opportunity.
Keywords: International relations